Capparis cartilaginea decne (capparaceae): isolation of flavonoids by high-speed countercurrent chromatography and their anti-inflammatory evaluation - Alsharif, Bashaer; Hante, Nadhim; Govoni, Bruna; Verli, Hugo; Kukula-Koch, Wirginia; Jose Santos-Martinez, María; Boylan, Fabio (Frontiers in Pharmacology, 2023)
Introduction:Capparis cartilaginea Decne. (CC) originates from the dry regions of Asia and the Mediterranean basin. In traditional medicine, tea of CC leaves is commonly used to treat inflammatory conditions such as rheumatism, arthritis, and gout. Due to the limited studies on the phytochemistry and biological activity of CC compared to other members of the Capparaceae family, this work aims to: 1) Identify the chemical composition of CC extract and 2) Investigate the potential anti-inflammatory effect of CC extract, tea and the isolated compounds. Methods: To guarantee aim 1, high-speed countercurrent chromatography (HSCC) method; Nuclear Magnetic Resonance (NMR) and High-Performance Liquid Chromatography coupled to Electrospray Ionisation and Quadrupole Time-of-Flight Mass Spectrometry (HPLC-ESIQTOF-MS/MS) were employed for this purpose. To guarantee aim 2, we studied the effect of the isolated flavonoids on matrix metalloproteinases (MMPs) −9 and −2 in murine macrophages. Molecular docking was initially performed to assess the binding affinity of the isolated flavonoids to the active site of MMP-9. Results and discussion:In silico model was a powerful tool to predict the compounds that could strongly bind and inhibit MMPs. CC extract and tea have shown to possess a significant antioxidant and anti-inflammatory effect, which can partially explain their traditional medicinal use.